Acute liver failure as the initial presentation of Wilson’s disease in a young adult: a case report - Sarbottam Koirala; Susant Thapa; Susmita Khadka Chhetri (Annals of Medicine & Surgery, 2026)
Acute liver failure is a rapidly progressive condition with high mortality that requires early identification and timely intervention. Wilson’s disease is a rare but important cause of acute liver failure in young individuals. We report a 31-year-old, previously healthy man who presented with acute jaundice and progressively altered sensorium and was found to have grade III hepatic encephalopathy with markedly elevated transaminases, hyperbilirubinemia, and severe coagulopathy. An extensive evaluation excluded viral, autoimmune, and drug-induced causes. Further workup revealed low serum ceruloplasmin levels and Kayser–Fleischer rings, supporting a diagnosis of Wilson’s disease. Despite intensive supportive management, the patient showed biochemical deterioration with declining transaminases and worsening synthetic dysfunction, indicating progressive hepatic necrosis. He was referred for urgent liver transplantation; however, due to financial constraints, definitive treatment could not be pursued, and the patient was lost to follow-up. This case highlights the critical impact of socioeconomic barriers on access to life-saving therapy and clinical outcomes.